STRATEGI KAMPANYE GANJAR RAMADHAN MELALUI PEMANFAATAN MODAL SOSIAL PADA PEMILU LEGISLATIF KABUPATEN CIANJUR TAHUN 2019 - Suntama, Erni Siti Rohayani; Djuyandi, Yusa (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan Bandung, 2022)
This paper analyzes the Ganjar Ramadhan campaign strategy through the use of social capital. Ganjar's social capital ownership was assessed using a qualitative descriptive study method. Data collection was carried out by literature study and field study through purposive interviews and examination of documents. The results of the study show that Ganjar's social capital includes Ganjar's figure; relationships and social networks owned by Ganjar and Ganjar's supporters. Its social capital can be utilized optimally through direct campaigns to the public in the form of door to door campaigns and direct mass campaigns. Utilization of social capital and proper communication played a role in his victory.